Experimental determination of single-crystal halite thermal conductivity, diffusivity and specific heat from −75 °C to 300 °C. (September 2015) - Urquhart, Alexander; Bauer, Stephen
Highlights: We measure thermal properties of a single crystal of halite from −75 °C to 300 °C. Thermal conductivity and thermal diffusivity decrease with increasing temperature. Specific heat shows no apparent temperature dependence. Results may be used to model and assess storage structures in rock salt formations. Results extend the known thermal conductivity of halite to cryogenic temperatures.